2015
DOI: 10.1074/jbc.m115.645200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Flavonoid Luteolin as a Repressor of the Transcription Factor Hepatocyte Nuclear Factor 4α

Abstract: Background: Flavonoids are naturally occurring compounds that can regulate certain transcription factors. Results: We identified the flavonoid luteolin as a repressor of HNF4␣ and revealed that dietary luteolin improves high-fat diet-induced metabolic disorder in mice. Conclusion: HNF4␣ is a target of luteolin. Significance: Modulation of HNF4␣ activity through luteolin may be of therapeutic value in atherosclerotic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Longterm clinical trials are decisive to confirm the beneficial effects of artichoke leaf extract administration upon cardiovascular outcomes. [88], [89], [90]]. Reduced HNF4α expression also decreases the synthesis of apoB, consequently decreasing VLDL and LDL levels [88].…”
Section: Resultsmentioning
confidence: 99%
“…Longterm clinical trials are decisive to confirm the beneficial effects of artichoke leaf extract administration upon cardiovascular outcomes. [88], [89], [90]]. Reduced HNF4α expression also decreases the synthesis of apoB, consequently decreasing VLDL and LDL levels [88].…”
Section: Resultsmentioning
confidence: 99%
“…7) Using this luciferase assay system, we identified that flavonoids such as flavones (luteolin, apigenin, chrysin, acacetin, and nobiletin) and flavonols (fisetin, kaempferol, and galangin) suppress the promoter activity of the MTP gene and that luteolin is the most effective flavonoid among the above compounds for suppression. 6) We also demonstrated that luteolin greater than 10 μM is required to suppress HNF4α target gene expression. Considering the low bioavailability of flavonoids, it would be preferable to find flavonoid derivatives that act at lower concentrations.…”
mentioning
confidence: 63%
“…On the contrary, we have previously demonstrated that luteolin functions as a repressor of HNF4α, and that luteolin treatment suppresses the expression of HNF4α target genes, including HNF4α. 6) Luteolin is able to form a complex with HNF4α, thereby leading to the suppression of HNF4α activity. 6) Currently, the reasons for this difference in results remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations